Harmonic scalpel versus titanium clips and l-hook in the ligation of cystic duct and artery and gall bladder dissection in laparoscopic cholecystectomy - Vijayvargiya, Anand; Jain, S. K.; Soni, Varsha (International Journal of Research in Medical Sciences, 2017)
Background: Laparoscopic cholecystectomy is a gold standard for gall bladder stone surgery. The Aim and objective of study was to compare the total duration of surgery, intraoperative complication like bile leak from cystic duct stump, spillage of bile from gallbladder and post op pain and abdomen distension and jaundice. Methods: Study was carried out in dept. of gen Surgery, Govt medical college Kota in yr. 2015-16 in a total of 50 patients with cholelithiasis with cholecystitis. Patient were equally divided randomly into two groups (a) Harmonic scalpel group and (b) Titanium Clip and L hook group. All patients with medical comorbidities, Concomitant CBD calculi, cirrhosis and portal HT were excluded from study. Intraoperatively adhesions, bile spillage from GB and cystic duct stump noted Postoperatively complain like pain abdomen, Jaundice, and fever were noted. Duration of hospital stay was observed. All results were statistically analyzed using Chi square and ANOVA test. Results: Both groups were comparable on the basis of age and sex distribution, as no statistically difference was noted (P value 0.867 and 0.999 respectively). Intraoperative findings were adhesions 5 in clip group and 7 in harmonic group. Spillage from gall bladder was 2 in Clip group and 3 in harmonic group. Mean duration of surgery was 65.20 min in clip group and 63.68 in harmonic group with no statistically significant difference in both the group (P Value 0.727). Average duration of hospital stay was similar in both the groups with a mean of 2.6 days. Postoperative complication was fever, abdomen pain and distension were 3,1,1 were respectively in the clip group and 3,2,2 respectively in harmonic group with the P value of 0.999 which was statistically insignificant. No CBD injury was noted in any case. Conversion to open cholecystectomy was not done in any case. On 1week and 1 month follow up 2 cases in clip group and 1 in HS group had collection in gall bladder fossa and none at I month. Conclusions: Harmonic scalpel offers an effective, alternative and safe method to cystic duct division and Gallbladder dissection from liver bed.